A capabilities analysis: degree mobility and the impact of returning South African alumni on their home country's sustainable development - Mwatunga, Carina Brigitte (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning)
The significance of sustainable development (SD) has gained increasing attention, particularly since introducing the Sustainable Development Goals (SDGs) in 2015. SDG 4 focuses on ensuring inclusive and high-quality education for all individuals, as well as the provision of equitable access to lifelong learning opportunities. In addition, SDG 4 recognises education as a fundamental element of societal progress and SD. Given the role of education in fostering economic growth, social cohesion, and individual empowerment, SDG 4 is a crucial component of global efforts to foster a more prosperous and equitable world. The primary focus of the study explained in this thesis was to address a specific aspect of Higher Education (HE) within the framework of the SDGs. While SDG 4 covers a wide range of targets, such as expanding scholarship opportunities for individuals from the Global South to study abroad, there remains a lack of comprehensive understanding of how pursuing a degree in a foreign country can influence graduates' potential contributions to sustainable development (SD) upon returning to their home countries. Moreover, despite researchers highlighting the need for attention to this topic, it has not received adequate focus thus far. Therefore, drawing upon the framework of the capability approach (CA) to sustainable development, the study explored whether returning graduates could contribute to SD in South Africa. To integrate the concepts of SD and CA, the study developed a framework for a responsible agent (RA), which was facilitated through previous studies. This framework provides a set of capabilities that are essential for supporting SD in South Africa. Based on this framework, the study comprehensively explored the experiences of postgraduate students and their potential to contribute to SD in South Africa. The study drew on survey data, semi structured interview, and document analysis to gain insights into how the structures of six selected scholarships aligned with SD objectives. However, upon analysing the eligibility criteria of these scholarships, it became evident that they already take into account certain capabilities associated with the RA in candidates. Furthermore, the analysis revealed that these scholarships tend to favour candidates who exhibit the potential to succeed in their professional endeavours. Therefore, this selection bias may exacerbate the existing inequalities within the South African education system. By disproportionately supporting candidates with advantages or resources, the scholarships may inadvertently perpetuate the disparities in educational opportunities and hinder progress toward a more equitable system. After administering questionnaires to alumni who had received these six scholarships, they were asked to voluntary participate in semi-structured interviews. Thereafter, data obtained was combined with document analysis, questionnaires, and interviews were analysed drawing on the RA framework with a narrative inquiry approach. The analysis of the data gathered during interviews with alumni revealed that certain capabilities were demonstrated and developed because of their degree mobility (pursuing degrees in different locations). However, it was also observed that some capabilities were negatively impacted by this mobility. Thus, the findings suggested a nuanced relationship between degree mobility and the development of specific capabilities amongst alumni, warranting further investigation to understand the implications of degree mobility on various capabilities. The investigation of the study revealed that the structure of the selected scholarships is not fully aligned with SD and that some capabilities can be damaged through degree mobility. To ensure that the scholarships truly support SD, they would require restructuring and (1) lowering expectations and preparing alumni for an often rather difficult return to South Africa; (2) limiting the available scholarships to degree programmes that are less or not affordable at all in South Africa; (3) implementing a re-entry strategy for returning alumni to make the return more manageable; and (4) collecting more data to create a deeper understanding about the possible achievements of individual alumni.
Keywords: Sustainable development -- South Africa; Education, Higher; Sustainable Development Goals (Project); Capabilities approach (Social sciences); Agent (Philosophy); Graduate student mobility